Parâmetros oftálmicos em cachorro-do-mato (Cerdocyon thous, Linnaeus, 1766) - Renzo, Roberta [UNESP] (2015)
Crab-eating foxes (Cerdocyon thous) are one of the wild animals most attended in rehabilitation centers, making it imperative to extend current knowledge of morphophysiological parameters specific to the species. This study assessed the ophthalmic conditions of 16 crab-eating foxes (n=32 eyes). Eight individuals were clinically assessed, under chemical restraint, by the Schirmer tear test I (STT I), digital applanation tonometry (IOP), non-contact specular microscopy (corneal thickness, density, area and corneal endothelial cell hexagonality), ultrasound in A and B modes (biometrics, particularly axial diameter, anterior and vitreous chamber depths and lens thickness) and electroretinography (amplitudes and implicit times of a- and b-waves, in scotopic and photopic phases). Corneas, collected post mortem from another eight individuals, were evaluated histologically to determine cornea and epithelium thickness and the birefringence parameters (data regarding aggregation and orientation) of lamellar collagenous stromal fibers, using morphometry, polarized light and image analysis software. Birefringence parameters were quantified as gray average (GA) values. Regarding the STT I and IOP, mean values of 13.37±0.94 mm and 10.43±0.96 mmHg were respectively verified. The mean corneal thickness was 0.53±0.01 mm. The mean density and area values of corneal endothelial cells were respectively 2850.38±137.28 cell/mm2 and 389.00±0.17 μm2. The mean value for hexagonality was 60.06±4.66 %. Concerning biometrics, the following mean values were verified: axial diameter, 15.93±0.28 mm; anterior chamber depth, 3.29±0.14 mm; vitreous chamber depth, 6.61±0.21 mm; and lens thickness, 6.02±0.11 mm. Electroretinography in the low amplitude scotopic phase showed values for mean amplitude and b-wave implicit time (20 min adaptation) of 87.33±5.36 μV and 73.10±1.12 ms, respectively. In the high amplitude scotopic phase, the mean amplitude value ...